Struktur Bahasa dan Sikap Bahasa Etnik Ternate terhadap Etnik Lain - Rahma Do Subuh; Bakhtiar Majid (Universitas Khairun, 2018)
The acceptance of Malay is the beginning of the attitude of acceptance of the language by Ternate society. Language attitudes can be classified into two, namely positive attitudes and negative attitudes. A positive attitude in the form of loyalty to language and will determine language defense should be a negative attitude that will lead to language shift. This study aims to describe the attitude of acceptance of Ternate's ethnic language which has historically been described as an ethnic group that easily accepts and even absorbs new cultures that have come. With the attitude of acceptance, how is the pattern or structure of the language used when communicating with other ethnic speakers. This is what encourages researchers to conduct research related to the structure of language and cycles of language reception by Ternate ethnicity. This study uses a qualitative descriptive method, in which the object of research is human beings and circumstances that are influenced by humans whose study is carried out as skillfully as possible. This study also uses a holistic approach including structural, sociology and anthropology. Research results show that the dominant language structure used by ethnicities includes 1). The level of morphology namely words and phrases, 2) syntax includes the negative words. Whereas the language attitude has shown is a negative language attitude towards one's own language and vice versa shows a positive language attitude towards other languages. From the perspective of communication, the attitude of the language shown by ethnic Ternate shows a very high level of language accommodation. Keywords: structure, language, attitudes